NASALIZATION IN BALINESE VERBS/PENASALAN VERBA BAHASA BALI - I Nyoman Udayana (Aksara, 2020)
Abstract Balinese has two forms in relation to nasal pre xes. First, the initial segment of the verb root can be assimilated with the homorganic nasal and both coalesce. Second, the nasal pre x still assimilates with the rst segment of the verb root but forms a CC cluster. The data source of this study is Balinese dictionaries and analyzed by Optimality Theoretic (OT) so it was found that the af x nasal did not form a cluster with the rst segment of the verb root uniformly occurred in verbs where the rst segment is obstruent both voiced and voiceless while the one forming the cluster is the rst segment of a verb root which is realized by a sonorant. The rst phenomenon can be handled by the constraint * NC (obs) while the second one by violates linearity constraint, namely, Align-L (root) constraint. OT analysis also predicts that the ungrammaticality of an output verb structure ngmaang ‘to give’ due to fact that the correct underlying form baang is confused with its corresponding surface form. Keywords: nasalization, obstruent, sonorant, OT analysis Abstrak Bahasa Bali mempunyai dua bentuk dalam kaitannya dengan pre x nasal. Pertama, segmen awal dari akar verba bisa berasimilasi dengan nasal yang homorganik dan keduanya berkoalisi. Kedua, nasal pre ks masih berasimilasi dengan segmen pertama akar verba, tetapi membentuk klaster CC. Sumber data penelitian ini adalah Kamus Bahasa Bali dan dianalisis dengan Optimality Theoretic (OT) sehingga didapatkan bahwa nasal a ks yang tidak membentuk klaster dengan segmen pertama akar verba secara seragam hanya terjadi pada verba yang mana segmen pertamanya adalah obstruent, baik bersuara maupun tak bersuara sedangkan yang membentuk klaster adalah segmen pertama verba yang direalisasikan oleh segmen bertipe sonorant. Yang pertama bisa ditangani oleh konstrein *NC (obs), sedangkan yang kedua adalah secara jelas melangggar konstrein linieritas, yaitu Align-L (root). Analisis OT juga memprediksi ketidakgramatikalan bentuk-output verba ngmaang ‘memberi’ yang bentuk dasarnya yang benar adalah baang dikacaukan dengan bentuk output-nya. Kata kunci: penasalan, hambatan, sonoran, Analisis OT